Adoption of Knowledge Management System: A Study on How IGracias Should be Adopted for Telkom Campus - Dewi Rahmawati; Noerma Pudji Istyanto; Muhammad Nasrullah (Universitas Putra Indonesia YPTK Padang, 2020)
IGraciass is an integrated academic and non-academic management information system from the Telkom Education Foundation (YPT). Based on the vision and mission, the strategy and tagline of the Telkom Education Foundation is